Subsoil Compaction: A hidden form of Soil Sealing in Europe - Jones, Robert J. A.; Montanarella, Luca (Joint Research Centre, 2001)
There are two definitions of ‘soil sealing’: (I) ‘covering (sealing) the soil surface by impervious materials, e.g. concrete, metal, glass, tarmac and plastic’; and (II) ‘changing the nature of the soil such that it behaves as an impermeable medium, e.g. by compaction’. The main causes of soil sealing according to the first definition (I) are building development (e.g. industrial and residential premises) and transport (e.g. roads). Changing the nature of the soil such that it behaves as an impermeable medium (definition II) is an extension to include the potential effects of the passage of machinery (mostly agricultural) and the effects of heavy rainfall. Intensification of agriculture is now recognised as often having a detrimental effect on soils, not least the widespread development of compaction. The worst effects of compaction at the surface can be rectified relatively easily by cultivation but once subsoil compaction occurs, it can be extremely difficult and expensive to alleviate. It is now clear that the detrimental effects of subsoil compaction go far beyond agricultural concerns of a decrease in yield and increase in management costs. Environmental impacts include increased erosion risk, accelerated runoff and increased pollution. A preliminary attempt to assess the susceptibility of subsoils in Europe to compaction is presented here in the context of soil sealing. The resulting distribution is only the first stage in assessing the vulnerability of subsoils in Europe to compaction. The biggest problem with soil sealing as an environmental indicator is the difficulty of establishing the true extent at the regional and larger scales. However, subsoil compaction should not be ignored because it probably affects a larger area in Europe than urbanisation (land consumption) and in this respect it must be regarded as an important process of soil sealing.
Keywords: subsoil; compaction; soil; sealing; Europe